2019
DOI: 10.1002/btm2.10145
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of the dually thermoresponsive behavior of peptide‐based vesicles through modification of collagen‐like peptide domains

Abstract: Materials that respond to temporally defined exogenous cues continue to be an active pursuit of research toward on-demand nanoparticle drug delivery applications, and using one or more exogenous temperature stimuli could significantly expand the application of nanoparticle-based drug delivery formulations under both hyperthermal and hypothermal conditions. Previously we have reported the development of a biocompatible and thermoresponsive elastin-b-collagen-like polypeptide (ELP-CLP) conjugate that is capable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 92 publications
(241 reference statements)
0
18
0
Order By: Relevance
“…We have previously reported a select set of ELP-CLP conjugates that can self-assemble into either thermoresponsive vesicular (21,22) or nonthermoresponsive platelet-like nanostructures (23). The formation of these structures is mediated by the thermally mediated phase separation of the ELP domain in the center of a bilayer-like structure, with triple-helical CLP domains at the surfaces of the bilayer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously reported a select set of ELP-CLP conjugates that can self-assemble into either thermoresponsive vesicular (21,22) or nonthermoresponsive platelet-like nanostructures (23). The formation of these structures is mediated by the thermally mediated phase separation of the ELP domain in the center of a bilayer-like structure, with triple-helical CLP domains at the surfaces of the bilayer.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous work, we conjugated short synthetic ELPs (peptides, rather than polypeptides) with short synthetic triple-helical CLP domains and have shown that the association of the CLP triple helix substantially lowers the high inverse T t of the short peptide-based ELP domain into experimentally tractable and, in some cases, physiologically relevant temperature ranges ( 21 , 22 ). Subsequently, we demonstrated the formation of assembled ELP-CLP conjugates by tuning the hydrophobicity of ELP domains comprising (VPGXG) 4 , in which the number of repeats equipped with phenylalanine (F) or tryptophan (W) residues in the X position was varied ( 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is the main component of extracellular matrix (ECM), which can be extracted from animal bones and fascia through digestion, hydrolysis, and other processes (Shi et al, 2019 ; Mohammed et al, 2020 ). In the process of evolution, collagen retains the original amino acid sequence, and the scaffold material made by it has non-antigenicity, good biocompatibility in vivo , and permeability (Dunshee et al, 2020 ). Because the tissue composition of tendons is mainly composed of collagen fibers, the large fiber bundles are arranged in parallel, and their direction is consistent with the traction force they bear.…”
Section: Discussionmentioning
confidence: 99%
“…These studies highlight the utility of nonequilibrium processing on hierarchical self-assembly of synthetic peptides. Rational molecular design of CMPs to promote their assembly into highly ordered nanofibers, hydrogels, vesicles, and nanospheres have also been demonstrated. …”
Section: Peptide Self-assemblymentioning
confidence: 99%